2010
DOI: 10.1021/jz100707f
|View full text |Cite
|
Sign up to set email alerts
|

Onsager Revisited: Magnetic Field Induced Nematic−Nematic Phase Separation in Dispersions of Goethite Nanorods

Abstract: We found, using polarization microscopy and small-angle X-ray scattering, that for goethite, a low polydispersity suffices to form two separate nematic phases, while previous theory showed that this is only possible for mixtures of particles with extremely different lengths or diameters. Applying a critical magnetic field, which induces some of the goethite nanorods to rotate, leads to sufficient excluded volume between the particles to cause macroscopic phase separation between two orthogonal nematic phases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Moreover, we want to emphasize that, in contrast to Ref. 92 , being out-of-equilibrium is essential for the observed demixing in our system as one of the favored orientations is the shear-induced orientation.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Moreover, we want to emphasize that, in contrast to Ref. 92 , being out-of-equilibrium is essential for the observed demixing in our system as one of the favored orientations is the shear-induced orientation.…”
Section: Resultsmentioning
confidence: 72%
“…Although the aforementioned Onsager analysis relies on equilibrium arguments, it does suggest that demixing in the present nonequilibrium system is possible. Experimentally, a similar demixing has been realized in a system of nano-rods 92 , where a certain degree of polydispersity is required to induce particle misalignments. In contrast to that, in our study, the demixing occurs between monodisperse particles.…”
Section: Resultsmentioning
confidence: 95%
“…In LC phases this couples to the orientational and partial positional order, which for instance leads to the reorientation of the nematic phase by 90 o and promotes the formation of a columnar from a nematic LC phase [48]. A new type of nematicnematic phase separation into domains with particle director oriented either perpendicular or parallel to the applied field was also found, due to the fact that larger particles in a polydisperse sample start to reorient at a weaker magnetic field causing packing problems so that they spontaneously separate into a different phase [60]. Polydispersity also plays a role in the smectic phase [61] transforming to a columnar phase at high polydispersity and an intermediate smectic-Clike zig-zag structure at low polydispersity.…”
Section: External Fieldsmentioning
confidence: 99%
“…Therefore, the particles have the opposing tendencies to align with their long axis parallel to the field at a low magnetic field strength and to orient perpendicular to a higher magnetic field. This magnetic property of goethite nanorods has been [45][46][47][48][49][50][51][52]. Goethite nanorods form nematic phases in their aqueous suspensions.…”
Section: Liquid Crystalline Nanorodsmentioning
confidence: 99%
“…Magnetic field induced nematic-nematic phase separation in goethite nanorods has been demonstrated recently. Small angle X-ray scattering measurements proved that the two resulting nematic phases have orthogonal orientations, a uniaxial nematic phase with particles parallel to the field and a biaxial nematic phase with particles perpendicular to the field [52]. Maeda et al prepared monodisperse colloidal β-FeOOH particles and found that smectic ordering occurs over a wide region from evaporating suspensions of the particle on substrates.…”
Section: Liquid Crystalline Nanorodsmentioning
confidence: 99%